Obesogenic neighborhood environment is associated with body fat and low-grade inflammation in Brazilian children: could the mother's BMI be a mediating factor? - Mariana De Santis Filgueiras; Milene Cristine Pessoa; Josefina Bressan; Ariene Silva do Carmo; Aline Siqueira Fogal Vegi; Fernanda Martins de Albuquerque; Juliana Farias de Novaes (Cambridge University Press, 2024)
Abstract Objective: To evaluate the direct and indirect associations of obesogenic and leptogenic neighborhood environments with body fat, and pro- and anti-inflammatory adipokines in Brazilian children. Design: Cross-sectional study. The body fat distribution was assessed using dual-energy X-ray absorptiometry (DXA). Concentrations of leptin and adiponectin were measured. Four hundred meters (0·25 miles) road network buffer was the neighborhood unit used to assess the environmental characteristics around households. Obesogenic and leptogenic environments were the latent variables obtained from the observed characteristics. The mother's BMI, ultra-processed food consumption, and physical activity before and after school, were tested as mediating variables. A hybrid model of structural equations was used to test the direct and indirect associations of obesogenic and leptogenic environments with body fat, leptin and adiponectin concentrations. Setting: Urban area of Viçosa, Minas Gerais, Brazil. Participants: Children aged 8- and 9-years (n 367). Results: Obesogenic environment was directly associated with the mother's BMI (β: 0·24, P = 0·02) and the child's body fat (β: 0·19, P = 0·02). The mother's BMI and body fat mediated the association of the obesogenic environment with leptin concentrations (β: 0·05, P = 0·02). Conclusions: Obesogenic neighborhood environment was directly associated with body fat and mother's BMI, and indirectly associated with leptin concentrations in Brazilian children, mediated by the mother's BMI and body fat.